Planejamento dos gastos públicos: o caso dos departamentos didáticos da Universidade Federal de Santa Maria - Vieira, Marco Aurélio (2016)
The central theme of the work is directly related to the planning of public expenditure under the Federal University of Santa Maria, as an instrument of management and support tool for decision making. This study aimed to explain how is the planning and budget management of public expenditure by the managers of the Federal University of Santa Maria, specifically on the campus of Palmeira das Missões. The methodological procedures were case descriptive and exploratory study, with qualitative approach. Semi-structured interviews were applied to the heads of teaching departments, manager and accountant campus Palmeira das Missões. Besides the interviews, the on-site observation and documents were used as a support for the analysis and discussion of results. The results of the study show that planning is mainly the gathering of information concerning the priorities and demands. They stand out in managing the implementation of the expenditure observed in the subdivision: daily, passages, consumption and permanent; and finally, control occurs in a personal and informal way through spreadsheets, and also formally in charge of the specific sector. The budget management has proven dependent and restricted resources available to departments, getting the boss with little autonomy management. In addition, there is also the greater emphasis of the department heads in budget management with respect to planning and control, due to institutional procedures and aspects of legal proceedings. Based on these results, it is concluded that there is no documented planning and formalized in public spending in departments, the heads are used individual knowledge to the actions to plan spending.